Lepton Flavor Violating μ- - e- Conversion: An Overview - Verma, P.; Vivekanand, -; Chaturvedi, K. (Journal of Scientific Research, 2021)
The search for lepton flavor violation in charged lepton decays is a highly sensitive tool to look for physics beyond the Standard Model. Among the possible processes, µ-decays are considered to have the largest discovery potential in most of the standard model extensions. Many searches have been performed in the past, but no evidence has been found so far. In this paper, we have reviewed the current theoretical and experimental status of the field of muon to electron decay and its potential to search for new physics beyond the Standard Model. Future prospects of experiments for further progress in this field are also discussed.